Pengolahan Limbah Cair Industri Sablon dengan Metode Elektrokoagulasi - Lestari, Dinda Deli; winardi, Winardi; Widha Nugraheni, Putranty (Universitas Tanjungpura, 2026)
Wastewater from the screen-printing process contains concentrated dyes and heavy metals, such as hexavalent chromium (Cr⁶⁺), which are hazardous to the environment if discharged untreated. Electrocoagulation is a treatment method that uses an electric current to dissolve a metal electrode, which then reacts to form coagulants within the water. These coagulants bind and precipitate contaminant particles, such as dyes and heavy metal ions. This study aims to (1) determine the efficiency of the electrocoagulation method in reducing color and Cr⁶⁺ parameters; (2) analyze the effect of contact time variation; (3) determine the electrode lifespan; and (4) calculate the estimated energy consumption and cost. The process was conducted using an Iron (Fe) anode and an Aluminum (Al) cathode at a constant voltage of 12 V, with contact times of 30, 45, and 60 minutes. The results showed that the electrocoagulation process was significantly effective (p < .001) in improving wastewater quality. The process successfully reduced color with an efficiency exceeding 99% and Cr⁶⁺ concentration with an efficiency over 92%, while also significantly increasing the solution's pH. Analysis of variance (ANOVA) indicated that variation in contact time had a significant effect on pH (p = 0.024). However, extending the time from 30 to 60 minutes did not show a statistically significant effect on the removal efficiency of color (p = 0.156) or Cr⁶⁺ (p = 0.270), indicating that the null hypothesis (H₀) was accepted for these two parameters. Electrode dissolution efficiency ranged from 64.5% to 75.6%, and the lowest estimated energy cost was obtained at the 30-minute treatment, at IDR 31.36 per liter. This study concludes that electrocoagulation with an Fe anode and Al cathode is highly effective, and a 30-minute process duration is optimal for achieving high pollutant removal efficiencies of 99.43% for color and 99.47% for Cr⁶⁺ cost-effectively. Electrocoagulation has been proven effective and is potentially applicable to small to medium-scale wastewater treatment for screen-printing.